2021
DOI: 10.21203/rs.3.rs-904917/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Analysis of the Selection Criteria for Postgraduate Physician Assistant Residency and Fellowship Programs in the United States

Abstract: BackgroundThis study aims to investigate the admission criteria used by PA postgraduate education programs in selecting licensed PA applicants for postgraduate training in the United States. To our knowledge, there have been no previously published reports on selection criteria and/or other factors influencing postgraduate PA admission decisions. This study both draws on and builds upon previous research conducted by Vasco Deon Kidd et. al in exploring the characteristics of PA postgraduate education programs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For example, Hart and Bowen surveyed several hundred licensed NPs and reported that 90% of them felt either "well prepared" or "somewhat prepared" for practice upon completion of their NP program and expressed interest in transition-to-practice opportunities through a formalized training program such as a residency [9]. Although, there are several descriptive cross-sectional studies describing programmatic functions and educational characteristics of PA and NP postgraduate fellowship/residency programs [7,[10][11][12][13], the effect of PA and NP formalized specialty training on patient outcomes is unknown. Notwithstanding the fact that PA postgraduate residency/fellowship training has been around for nearly 50 years and NP residency training for almost two decades, some prospective applicants may be unaware of how to obtain information about these specialty training opportunities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hart and Bowen surveyed several hundred licensed NPs and reported that 90% of them felt either "well prepared" or "somewhat prepared" for practice upon completion of their NP program and expressed interest in transition-to-practice opportunities through a formalized training program such as a residency [9]. Although, there are several descriptive cross-sectional studies describing programmatic functions and educational characteristics of PA and NP postgraduate fellowship/residency programs [7,[10][11][12][13], the effect of PA and NP formalized specialty training on patient outcomes is unknown. Notwithstanding the fact that PA postgraduate residency/fellowship training has been around for nearly 50 years and NP residency training for almost two decades, some prospective applicants may be unaware of how to obtain information about these specialty training opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no national resident matching program or centralized application-processing service available to licensed PAs and NPs interested in pursuing postgraduate residency/fellowship training [10]. Therefore, prospective orthopedic surgery PA and NP applicants often use the internet as a source of information when researching and applying for these specialty training programs.…”
Section: Introductionmentioning
confidence: 99%
“…PAs are trained as generalist in the medical model while NPs are trained based on a speci c population foci. Postgraduate training options in the form of residencies or fellowships exist but are not a requirement for PA and NP entry-level practice or state licensure [3][4][5]. PAs and NPs clinically practice in various areas of medicine and are integral to a highly effective team-based care model.…”
Section: Introductionmentioning
confidence: 99%